New Stability Estimates of Solutions to Strong Damped Wave Equation with Logarithmic External Forces - Houma, Nabil; Zennir, Khaled; Beniani, Abderrahmane; Djebabela, Abdelhak (Discontinuity, Nonlinearity, and Complexity, 2026)
In ths paper, we consider a new stability results of solutions to class of wave equations with weak, strong damping terms and logarithmic source in $\mathbb{R}^n$. We prove general stability estimates by introducing suitable Lyapunov functional.